Using Picus® Sonic Tomograph to assess the health state of trees of monumental sizes - Durlak, Wojciech; Dudkiewicz, Margot; Pudelska, Krystyna; Dąbski, Marek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
The aim of the study was to examine the usefulness of The Picus 3 Sonic Tomograph to assess the health state of trees of monumental sizes, which are an important part of the cultural landscape. In the study there were selected tree species Tilia cordata, Gingko biloba and Ulmus glabra growing in the vicinity of Lublin in different habitat conditions. Changes in the internal structure of the tree trunks were shown on the colour tomograms. Two tested specimens of Tilia cordata located in Radawiec Duży were intended to be cut down due to the construction of the ring road of Lublin. This made it possible to compare the obtained tomograms with the actual state of the inside of tree trunks after cutting down the examined trees. The results of Picus tomography Ulmus glabra and Gingko biloba growing in the historic park in Czesławice were confirmed by a visual assessment of trees. In each case the number of installed sensors influenced the image resolution and accuracy of the obtained tomograms. Diagnostics using sound waves is important in assessing the state of health of each tree, but it is especially recommended for testing of valuable trees. It allows for early diagnosis and selection of such protective actions to reduce to a minimum the destructive impact study on the body of the plant.